Gross Anatomical Investigation on Lymphnodes of the Abdominal and Pelvic Regions in Buffaloes (Bubalus bubalis) - Sanjay Chouhan,; Balwant Meshram,; Hemant Joshi,; Sandeep Kumar,; Ankit Damor,; Poonam Saini,; Pawan Kumar, (Indian Journal of Veterinary Anatomy, 2026)
The present study was carried out to elucidate gross anatomical study of lymph nodes in the abdominal and pelvic regions of buffaloes (Bubalus bubalis)” for basic as well as applied purposes. The lymph nodes namely pre-femoral, popliteal, mesenteric and superficial inguinal (scrotal and supramammary) lymph nodes of buffaloes consisted of capsule which covered whole parenchyma except at hilus. The presence of obstructive neighboring tissues close to the lymph nodes, thick skin, and the animal’s resistant behaviour were the primary hurdles when palpating these lymph nodes in living animals. Under the skin, the pre-femoral and superficial inguinal lymph nodes were the most clearly defined and easily palpable. The carcass’s lymph node position was largely consistent with reports of similar locations in cattle. The lymph nodes were found single on each side but mesenteric lymph node was presented along the mesentery near the jejunum and ilium. However, prefemoral lymph nodes were occasionally found in pairs. The lymph nodes were mostly oval or bean shaped; however some were elongated and flat. The mean biometrical value in respect to length, width, thickness and weight were slightly variable in right and left sides.